(untitled) (Bangladesh Journal of Public Administration, 2022)
This study attempts to investigate how customers view organic food. This essay also tries to investigate the issues with promoting organic farming. Lack of knowledge about organic technology and consumer distrust of goods and advertising strategies are among the important problems. It is discovered that a variety of factors affected people’s decisions to buy organic food. Health and environmental awareness were positively correlated with educational attainment. The majority of consumers expressed interest in learning more about the production of organic foods, and it is evident that organic agriculture might lessen the harmful effects of chemical agriculture. The majority of customers expressed a lack of trust in organic food products by being unwilling to pay more for quality assurance and organic certification. Furthermore, there is a significant opportunity to meet the local demand for organic food, notably on the vast agricultural acreage in Rajshahi. Rajshahi has the chance to increase organic food production thanks to the lower wage, which will afterwards lead to the creation of good jobs. The barriers to the growth of the organic markets were recognized as ignorance, ecological consciousness, consumer trust, accreditation, quality control mechanisms, current technology, information literacy, storage capabilities, and crop insurance. The agricultural market chain, which is made up of many intermediary organizations, is also vulnerable. A big benefit of producing organic products that require meticulous care is the accessibility of cheaper labor forces.